Effect of fabric orientation on mechanical properties of cotton fabric reinforced geopolymer composites - Alomayri, T.; Shaikh, Faiz; Low, It Meng (Elsevier Ltd, 2014)
This paper presents the thermal, mechanical and fracture behaviour of fly-ash based geopolymer composites reinforced with cotton fabric (0–8.3 wt.%). Results revealed that fly-ash based geopolymer can prevent the degradation of cotton fabric at elevated temperatures. The effect of cotton fabric orientation (i.e., horizontal or vertical) to the applied load on flexural strength, compressive strength, hardness and fracture toughness of geopolymer composites is also investigated. The results showed that when the fabricsare aligned in horizontal orientation with respect to the applied load, higher load and greater resistance to the deformation were achieved when compared to their vertically-aligned counterparts.